The study of radio frequency interference (RFI) for radio astronomy in some remote locations in Peninsular Malaysia / Syed Bahari Ramadzan bin Syed Adnan - Syed Adnan, Syed Bahari Ramadzan (2010)
Radio Frequency Interference (RFI) is the main parameter to find the best site for radio astronomy research development. The increasing levels of RFI will pose a big problem for researchers in the radio astronomy field. The radio astronomers are encouraged to choose sites as free as possible from interference. In this research we aimed to survey the RFI at frequency 1 MHz-2000MHz to look the overview of the RFI profile and at frequency 1419 MHz-1421 MHz to monitor the RFI profile at Hydrogen line frequency (1420.4 MHz). We chose Peninsular Malaysia as the research area for RFI observation. We have used the Geographical Information System (GIS) software to find and create the lowest RFI mapping area in Peninsular Malaysia. Proper decision-making processes for selection of lowest RFI sites requires collection of information about various parameters like the density of Malaysian citizen‘s data, communication transmitter station‘s area data, road network, and land contour data. After recognizing a few suitable areas we will commence to the sites and construct the RFI observations. An RFI survey at that selection site will be done using an omni-directional discone antenna in wideband and narrowband methods. This method provides a basic way of determining the strength of the RFI at observation sites. Eventually, the best area base will be decided from the observations. The results of this experiment will support the development of the first radio telescope in Malaysia and provide the suitable area for radio astronomical observations in Peninsular Malaysia. From the GIS analysis, we have found three potential sites. They are Sekayu (Latitude: 04o57.967‘ N, Longitude: 102o57.332‘ E), Bertam (Latitude: 05o09.991‘ N, Longitude: 102o02.764‘ E) and Jelebu (Latitude: 03o 03.108‘ N, Longitude: 102 03.912‘ E). The RFI results showed that Sekayu is the best site for future radio astronomical observation in Peninsular Malaysia with average signals in wideband as -152.32 dBWm-2Hz-1 which is equivalent to 5.86 x 10-16 Jy and in narrowband as -153.93 dBWm-2Hz-1 which is equivalent to 4.04 x 10-16 Jy.